2012
DOI: 10.1371/journal.pone.0045805
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidative Stress Induced Inflammation Initiates Functional Decline of Tear Production

Abstract: Oxidative damage and inflammation are proposed to be involved in an age-related functional decline of exocrine glands. However, the molecular mechanism of how oxidative stress affects the secretory function of exocrine glands is unclear. We developed a novel mev-1 conditional transgenic mouse model (Tet-mev-1) using a modified tetracycline system (Tet-On/Off system). This mouse model demonstrated decreased tear production with morphological changes including leukocytic infiltration and fibrosis. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
4

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 44 publications
1
79
1
4
Order By: Relevance
“…The structure of the osmolyte erythritol was found to resemble mannitol, a well-known antioxidant, 47 and oxidative damage has been implicated in the pathogenesis and development of dry eye. 48,49 And recently, L-carnitine was found to protect the corneal epithelial cells from apoptosis induced by hyperosmotic stress. 50 Betaine, a metabolite of plant and animal tissues, is considered a protectant against salt and temperature stress in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the osmolyte erythritol was found to resemble mannitol, a well-known antioxidant, 47 and oxidative damage has been implicated in the pathogenesis and development of dry eye. 48,49 And recently, L-carnitine was found to protect the corneal epithelial cells from apoptosis induced by hyperosmotic stress. 50 Betaine, a metabolite of plant and animal tissues, is considered a protectant against salt and temperature stress in plants.…”
Section: Discussionmentioning
confidence: 99%
“…161 Infiltration with autoreactive T cells and oxidative stress have also been observed in the aged lacrimal gland, indicating that aging is associated with inflammation and is not simply a degenerative process. 98, 137, 162166 These studies suggest that similar to the ocular surface, a vicious cycle of inflammation and apoptosis involving infiltrating cells and glandular acinar cells perpetuates LG inflammation leading to glandular dysfunction in SS and age-related dry eye.…”
Section: Dry Eye – a Multifactorial And Self-perpetuating Inflammatormentioning
confidence: 98%
“…oxidative stress models to confirm the relationship between ROS and dry eye. 48 Tobacco smoking is believed to be a risk factor for dry eye, and it may be attributable to oxidative stress. Clinical studies have shown that tobacco smoking induces ROS in the ocular surface by initiating inflammation, resulting in dry eye.…”
Section: Oxidative Stress and Dry Eyementioning
confidence: 99%